Restrictions on Employer Access to Employee Health Data - Bielak-Jomaa, Edyta (Acta Universitatis Lodziensis. Folia Iuridica, 2025)
One of the key duties of the employer is to ensure safe and hygienic working conditions for employees, which means that he must ensure that the health status of employees performing work does not adversely affect the health and lives of others. Achieving this objective therefore requires the employer to have knowledge of the employee's health status. By gaining access to information on health status, the employer simultaneously collects and processes personal data on the health of employees. However, access to the data is not unfettered and its scope is limited to strictly defined information. The purpose of this article is to determine the nature of these restrictions from the perspective of personal data protection.